2019
DOI: 10.1097/md.0000000000014378
|View full text |Cite
|
Sign up to set email alerts
|

The triad of diabetes ketoacidosis, hypertriglyceridemia and acute pancreatitis. How does it affect mortality and morbidity?

Abstract: The triad of acute pancreatitis (AP) coexisting with diabetes ketoacidosis (DKA) and hypertriglyceridemia (HTG) has been reported, but no impact on mortality has been found to date. We aim to assess if patients with this triad are at a higher inpatient mortality compared to patients with acute pancreatitis only. Retrospective cohort. The National Inpatient Sample (NIS) database from 2003 to 2013 was queried for patients with a discharge diagnosis of AP and presence of DKA and HTG was ascertained bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 5 publications
3
17
0
Order By: Relevance
“…26 A study of 2.8 million patients with acute pancreatitis indicated that compared with simple HTG-AP patients, DKA and HTG triad had significantly higher mortality, multiple organ failure rate, longer hospitalization periods, and higher costs in AP patients. 36 In the present study, there were 20 cases of DKA (10%). The incidence of DKA in the TG≥11.2 mmol/L group was 18.75%, which was higher than those of the other three groups.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…26 A study of 2.8 million patients with acute pancreatitis indicated that compared with simple HTG-AP patients, DKA and HTG triad had significantly higher mortality, multiple organ failure rate, longer hospitalization periods, and higher costs in AP patients. 36 In the present study, there were 20 cases of DKA (10%). The incidence of DKA in the TG≥11.2 mmol/L group was 18.75%, which was higher than those of the other three groups.…”
Section: Discussionsupporting
confidence: 44%
“…AP, DKA, and HTG are often mutually causal and interact with each other to form a "death triangle". 36 The state of high blood sugar, high blood ketones, dehydration, electrolyte disturbances, and metabolic acidosis make patients prone to hyperosmolar coma and eventually life-threatening circumstances. 26 A study of 2.8 million patients with acute pancreatitis indicated that compared with simple HTG-AP patients, DKA and HTG triad had significantly higher mortality, multiple organ failure rate, longer hospitalization periods, and higher costs in AP patients.…”
Section: Discussionmentioning
confidence: 99%
“…On admission, our patient presented many risk factors such as obesity, familiar hypertriglyceridemia, sedentary lifestyle, and excessive sugar-sweetened soft drinks daily intake. Classical triad of DKA-HTG-AP was confirmed, a rare evidence described with 11% prevalence in overall AP patients, unfortunately associated with higher rate of inpatient mortality, multiorgan failure, parental nutrition requirement, hospital charges, and longer hospital length of stay [17]. Moreover, the association of negative autoimmune markers and good β-cell function assigned a 54% probability of developing ketones in our patient [3].…”
Section: Discussionsupporting
confidence: 71%
“…In agreement with our study finding, another largescale population-based study investigating HTG-induced pancreatitis found lower mortality in patients with acute pancreatitis and HTG. These findings lend credibility to the possibility that the commonly accepted idea of HTG-induced pancreatitis being associated with increased disease severity when compared to other causes of pancreatitis is incorrect [26].…”
Section: Discussionsupporting
confidence: 54%